Effect of Slow Stroke Back Massage on Anxiety of Older Women with Breast Cancer Undergoing Chemotherapy - Massoumeh Basiri; Farideh Bastani; Hamid Haghani; Leili Rahmatnejad (Iran University of Medical Sciences, 2016)
Background: Anxiety is the most prevalent psychological side effect of breast cancer and chemotherapy. This study aimed to determine the effect of slow stroke back massage (SSBM) on the anxiety of old female patients with breast cancer undergoing chemotherapy. Methods: In this quasi-experimental study, 80 elderly women with breast cancer undergoing chemotherapy were enrolled by continuous sampling method. They were divided into two groups of experiment and control. The experiment group received three 15-min sessions of SSBM for 3 consecutive days. The data collection instrument was geriatric anxiety scale, which was used to measure the anxiety of the subjects. Descriptive and inferential statistics were used to analyze the data with 95% of confidence level in SPSS V.21. Results: There was no significant difference between two groups in terms of anxiety and they were quite homogeneous before the intervention (P=0.220). The average score of anxiety level reduced significantly from 40.97 before intervention to 30.47 after the intervention in the experiment group compared to the control group and the results were significant (P<0.001). Furthermore, no significant reduction was found in the average anxiety level of the control group before and after the intervention (P=0.457). There was also a significant difference between the average score of anxiety levels of the two groups after the intervention (P< 0.001). Conclusion: Because of the significant reduction of anxiety in the experiment group by using SSBM, this method can be recommended as an easy, accessible, and affordable method to apply on elderly women with breast cancer undergoing chemotherapy. Also, it is recommended that SSBM be used by nurses working with this group of women.